2022
DOI: 10.1002/ptr.7689
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of 4‐geranyloxy‐2,6‐dihydroxybenzophenonel on DSS‐induced ulcerative colitis in mice via regulation of cAMP/PKA/CREB and NF‐κB signaling pathways

Abstract: Hypericum sampsonii Hance has traditionally been used to treat enteritis and diarrhea. As one of the main benzophenones isolated from H. sampsonii, 4‐geranyloxy‐2,6‐dihydroxybenzophenonel (4‐GDB) has been shown to possess anti‐inflammatory effects. However, the therapeutic effect and potential mechanisms of 4‐GDB in ulcerative colitis (UC) remain unclear. This study aimed to evaluate the role of 4‐GDB in UC using a dextran sulfate sodium‐induced colitis mouse model. Intragastric administration of 4‐GDB (20 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Besides, benzophenone derivatives have also been shown to be important in the anti-inflammatory effects of H. sampsonii . Recently, our group investigated the therapeutic effect and potential mechanisms of 4-geranyloxy-2,6-dihydroxybenzophenonel (4-GDB, 133 ) on DSS-induced ulcerative colitis in mice ( Wang et al, 2023 ). This study showed that intragastric administration of 4-GDB (20 mg/kg/day) for 8 days significantly attenuated colonic injury, reduced the expression of inflammatory mediators, and improved colonic barrier function in mice with colitis.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Besides, benzophenone derivatives have also been shown to be important in the anti-inflammatory effects of H. sampsonii . Recently, our group investigated the therapeutic effect and potential mechanisms of 4-geranyloxy-2,6-dihydroxybenzophenonel (4-GDB, 133 ) on DSS-induced ulcerative colitis in mice ( Wang et al, 2023 ). This study showed that intragastric administration of 4-GDB (20 mg/kg/day) for 8 days significantly attenuated colonic injury, reduced the expression of inflammatory mediators, and improved colonic barrier function in mice with colitis.…”
Section: Biological Activitiesmentioning
confidence: 99%